ANTI-ULCER ACTIVITY OF THE AQUEOUS EXTRACT OF PORTULACA RACEA L.IN ASPIRIN PLUS PYLORIC LIGATION INDUCED ULCER IN ALBINO RATS. - BANYLLA SN; S. RITA; A. SUBHALAKSHMI DEVI; U. DHARMARAJA MEETEI; KH. SANIA MONICA; A. PFUZIA (International Journal of Pharma and Bio Sciences, 2013)
The anti-ulcer activity of the aqueous extract of Portulaca oleracea L. was studied in aspirin plus pylorus ligation induced ulcer in albino rats. Eighteen healthy albino rats were divided into 3 groups of six animals each group. Group I (control) received 1ml/200 gram of 2% gum acacia, Group II (standard) received omeprazole 2 mg/kg body weight, Group III received the test drug i.e, the extract at 500 mg/kg body weight, and all groups received aspirin (200 mg/kg body weight). All the drugs were suspended in 2% gum acacia in distilled water and given orally at a uniform volume of 1ml/200 gram daily for 5 days before pyloric ligation. The anti-ulcer activity was evaluated by four parameters i.e, Ulcer Index, pepsin activity, free and total acidity, and gastric barrier mucus secretion. The extract shows significant anti-ulcer activity when compared with the control and comparable efficacy with the standard. This study shows that the aqueous extract of Portulaca oleracea L. has significant anti-ulcer activity.